Perceived-air pollution and self-reported health status: a study on air pollution-prone urban area of Bangladesh - Rahman, Md Mostafizur; Hasanuzzaman, A. B. M.; Chisty, Musabber Ali; Alam, Edris; Islam, Md Kamrul; Islam, Abu Reza Md. Towfiqul (Frontiers in Public Health, 2025)
Air pollution is a serious health concern in rapidly developing countries like Bangladesh. This study investigates the correlation between self-reported health issues related to air pollution and perceived air pollution among adult Bangladeshis. A face-to-face questionnaire was conducted with 398 adult residents who had lived in their current location for at least 3 years. The survey assessed self-reported health using 13 specific air pollution-related health problems. A linear regression model was then used to analyze factors affecting air pollution-related health status. Our findings reveal correlations between perceived air pollution and health issues. 90% of respondents reported air-polluted environments in their area, with the majority citing multiple sources (42%) of air pollution. Construction activities emerged as a predominant concern, identified by 31% of participants as a primary source of air pollution. Demographic factors play a crucial role in contributing to air pollution-related health problems. Notably, older age groups reported significantly higher health issues compared to their younger counterparts. Residents of Mirpur’s residential neighborhood experienced fewer health problems related to air pollution, indicating the influence of urban planning on public health. This interdisciplinary approach offers a comprehensive view of Bangladesh’s air pollution crisis, combining environmental science and public health perspectives. The findings emphasize the need for targeted policy interventions, including stricter regulations on construction activities to mitigate their impact on air quality, tailored public health interventions for vulnerable populations (especially older adults), and urban planning strategies that reduce exposure to air pollution in residential areas. Future research should investigate the long-term health impacts of chronic air pollution exposure and evaluate the effectiveness of various mitigation strategies. Addressing these issues can help create healthier, more resilient urban environments.